A Quantum Dot Array for Enhanced Tricolor Liquid-Crystal Display - Yikun Liu; Juan Lai; Xiaonan Li; Ying Xiang; Juntao Li; Jianying Zhou (IEEE Photonics Journal, 2017)
In the traditional liquid crystal display, at least two-thirds of the energy is wasted by tricolor separation color filter array due to its blocking working principle. In this paper, a well arrangement quantum dots (QD) array, which is excited by blue back light, was fabricated to spatially separate the red-green-blue (RGB) color. This QD array is further placed onto traditional color filter array, by matching the corresponding color filter pixel, in order to eliminate the blue light cross talk. In this case, the energy efficiency of this QD active color filter array no longer depends on its geometric arrangement and absorption properties, but depends on the quantum yield of QDs. Furthermore, 90% Adobe RGB color gamut can be achieved. One advantage of our fabrication method is synthesizing the QDs array onto the substrate directly, without the requirement of dissolving the QDs into other media. This technique may provide a new method to obtain higher color separation efficiency in liquid crystal display (LCD) than the traditional color filter matrix by enhancing the quantum yield of QDs.